(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article deals with the semantic features of Russian adjectives golden, golden, golden and their functioning in Russian poetry. It is argued that their metaphorical meaning changed in different time periods and with different authors (Alexander Pushkin, Anna Akhmatova, Bella Akhmadullina, Bulat Okudzhava, Vladimir Vysotsky). The purpose of the article is to conduct a comparative analysis of the use of these words in Russian poetry of the 19th and 20th centuries. It is argued that over time, the main metaphorical shifts in the use of the analyzed words are associated both with the individual style of the author and with the general turn towards a pragmatic society in the second half of the 20th century. Thus, the analysis of the indirect meanings of these adjectives reveals the differences in the Russian linguistic picture of the world in different periods of time.